2010
DOI: 10.1021/es1025382
|View full text |Cite
|
Sign up to set email alerts
|

Fractionating Nanosilver: Importance for Determining Toxicity to Aquatic Test Organisms

Abstract: This investigation applied novel techniques for characterizing and fractionating nanosilver particles and aggregates and relating these measurements to toxicological endpoints. The acute toxicity of eight nanosilver suspensions of varying primary particle sizes (10-80 nm) and coatings (citrate, polyvinylpyrrolidone, EDTA, proprietary) was assessed using three aquatic test organisms (Daphnia magna, Pimephales promelas, Pseudokirchneriella subcapitata). When 48-h lethal median concentrations (LC50) were expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
145
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(158 citation statements)
references
References 23 publications
12
145
1
Order By: Relevance
“…While a substantial number of studies describe the lethal toxicity of various forms of silver, including silver nitrate (AgNO3) and silver nanoparticles (AgNP) (Allen et al, 2010, Hoheisel et al, 2012, Kennedy et al, 2010, the information on chronic toxicity to aquatic organisms is scarce. Also the mechanisms of nanosilver toxicity are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…While a substantial number of studies describe the lethal toxicity of various forms of silver, including silver nitrate (AgNO3) and silver nanoparticles (AgNP) (Allen et al, 2010, Hoheisel et al, 2012, Kennedy et al, 2010, the information on chronic toxicity to aquatic organisms is scarce. Also the mechanisms of nanosilver toxicity are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…AgNPs have emerged as a topic of environmental concern as they could have unintended detrimental ecological impacts, due to their effective biocidal properties. Research regarding the potential mechanisms of toxicity of AgNPs is still emerging, with most of the available data involving freshwater species (Kennedy et al, 2010;Laban et al, 2010;Scanlan et al, 2013;Yang et al, 2012), prokaryotic and eukaryotic microorganisms (Ivask et al, 2014;Morones et al, 2005), as well as some mammalian cell lines and viruses (Cha & Myung, 2007;Kittler et al, 2010). Unfortunately, few studies have involved soil-dwelling organisms, even fewer specifically used AgNPs (Shoults-Wilson et al, 2011a,b,c;Tsyusko et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This confirmed that the Ag þ released from the AgNPs induced significant metabolic alterations. Kennedy et al (2010) indicated the importance of free silver ions as a major source of toxicity of AgNPs to D. magna and Pimephales promelas. Zhao and Wang (2012) also attributed toxicity of AgNPs to daphnids mainly to the release of soluble Ag, as similar 48 h LC50s were obtained for lactate-coated AgNPs, PVPcoated AgNPs and AgNO 3 , when the daphnids were exposed to the soluble Ag released from AgNPs.…”
Section: Discussionmentioning
confidence: 99%